The Role of the Sembalun Community Development Center in Increasing Ecological Awareness and Economic Development of the Sembalun Village Community - Handayani, Latifah; Yahya Himni, M Saleh (English and Tourism Studies, 2023)
Humans, nature, animals, and plants are a unit that forms the life cycle. These four elements are a condition of balance for the survival of life. If one is disturbed, the other elements will also be shaken. Environmental problems that are happening are also caused by the very apprehensive economic conditions of the people. Because of poverty, nature is the only object seen as capable of liberating it from the myriad of economic problems increasingly entangling in life. If so, then the balance of nature for the next generation's life is no longer thought of. The increasingly brutal behavior of society causes various kinds of life problems to emerge. Therefore, in this study, researchers will discuss ecological awareness and economic development carried out by social institutions, namely the Sembalun Community Development Center, which is currently on the island of Lombok, to be precise in Sembalun village, a village around the slopes of Mount Rinjani. The method used in this study is qualitative, descriptive analysis. In this study, it can be seen that SCDC plays an essential role in maintaining the balance of nature and the socio-economic welfare of the community. Keywords: awareness, ecology, development